Nylon material for copper bar coating and preparation method thereof
By adding polyamide-polyether, polyether elastic body, cluster PP and other components to add polyamide-polyether, solve the problem of insufficient adhesion for nylon 1012 in copper-rowing materials, and so on. Cover and low -cost production.
Patent Information
- Application Number
- CN202411351172.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing nylon 1012 has defects such as insufficient adhesive strength, easy foaming, easy bending, whitening, and unresisting high temperature and easy color change in the copper strip coating material.
By adopting long carbon chain nylon 1012 as the main component, and adding polyamide-polyether's cluster elastic body, cluster PP, thermal stabilizer, lubricant and color powder, improve the flexibility, adhesion and bending folding of the material performance.
The low cost and high performance covering of nylon materials is achieved, and the adhesion, impact resistance and chemical resistance of the material are improved, and the problems of easy to turn white and not high temperature.
Smart Images

Figure BDA0005062402620000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nylon materials, and in particular to a nylon material for copper busbar coating and a preparation method thereof. Background Art
[0002] Copper busbar is a high current conductive product made of copper. It is generally a long conductor with a rectangular or chamfered (rounded) rectangular cross-section to avoid tip discharge. Copper busbars are widely used in electrical engineering such as high and low voltage electrical appliances, switch contacts, power distribution equipment, bus ducts, etc. They can also be used in ultra-high current electrolytic smelting projects such as metal smelting, electrochemical plating, and chemical caustic soda. The main function of copper busbars is to transmit current and connect electrical equipment. It plays a vital role in electrical equipment, especially in complete sets of power distribution equipment. Copper busbars are widely used due to their excellent conductivity and stability.
[0003] The outside of the copper busbar is generally coated with a layer of insulating material to play the role of insulation and heat insulation. Nylon has excellent electrical insulation properties, high volume resistivity, and high breakdown voltage resistance, making it an excellent electrical insulation material. Traditional copper busbar coating materials mainly use nylon 12. The scientific name of nylon 12 is polylaurolactam. The basic raw material of its polymerization is butadiene, which is a semi-crystalline-crystalline thermoplastic material. However, most of the existing extrusion coating materials based on nylon 12 rely on imports and are expensive, while the domestic experience or technology in the synthesis of nylon 12 raw materials, product stability and production capacity control are relatively lacking and immature. Therefore, the production cost of nylon 12 is high and the source is limited, which to a certain extent limits the product competitiveness of the coating material with it as the main component. Nylon 1012 is similar to nylon 12 in molecular structure, basic properties and application fields, so the solution of using nylon 1012 to replace nylon 12 has received widespread attention. However, nylon 1012 has the disadvantages of insufficient adhesion, easy blistering, easy bending and whitening, poor heat resistance and easy color change when used as copper busbar coating materials. Therefore, a modified material for nylon 1012 used as copper busbar coating materials is urgently needed to overcome the above-mentioned disadvantages of nylon 1012 used as copper busbar coating materials. Summary of the invention
[0004] The present invention aims to provide a nylon material for copper busbar coating and a preparation method thereof. By adopting nylon 1012 with lower production cost and wider source to replace nylon 12, the production cost of the material is reduced. At the same time, by adding polyamide-polyether elastomer and copolymer PP, the flexibility, adhesion, bending resistance, non-whitening and other properties of the material are improved.
[0005] To achieve the above object, the present invention proposes the following technical solutions:
[0006] A nylon material for copper busbar coating comprises the following components by weight: 101280-90 parts of long carbon chain nylon, 3-8 parts of polyamide-polyether copolymer elastomer, 5-10 parts of copolymerized PP, 1-3 parts of heat stabilizer and 0.5-1.5 parts of lubricant.
[0007] As a preferred technical solution of the present invention, the number of methylene groups between two amide groups in the main chain repeating unit of the long carbon chain nylon 1012 is 10-15.
[0008] As a preferred technical solution of the present invention, the polyamide-polyether copolymer is a segmented block copolymer composed of polyamide hard segments and polyether soft segments arranged in segments, wherein polyamide is a crystalline high-melting point hard segment and polyether is an amorphous soft segment with a low glass transition temperature.
[0009] As a preferred technical solution of the present invention, the copolymer PP is a random copolymer PP.
[0010] As a preferred technical solution of the present invention, the heat stabilizer is a non-copper salt heat stabilizer.
[0011] As a preferred technical solution of the present invention, the lubricant is one or more of stearic acid, ethylene bisstearamide, and polyolefin wax.
[0012] As a preferred technical solution of the present invention, it also includes 0.4-0.8 parts of color powder.
[0013] The present invention also provides a method for preparing a copper busbar coated with a nylon material, comprising the following steps:
[0014] Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, copolymer PP, heat stabilizer, lubricant and color powder according to weight, and dry the long carbon chain nylon 1012 at 90° C.-100° C. for 2-3 hours;
[0015] Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix;
[0016] Step 3: hot-melt extrude the premix in step 1 through a twin-screw extruder, draw into strips, cool, and pelletize to obtain the nylon material.
[0017] As a preferred technical solution of the present invention, the processing temperature of the twin-screw extruder is 240°C-260°C.
[0018] It can be seen from the above technical scheme that the technical scheme of the present invention provides a nylon material for copper busbar coating and a preparation method thereof. In this technical scheme, nylon 1012 is used instead of nylon 12. Compared with nylon 12, nylon 1012 has lower production cost and wider source, which makes the overall cost of the material lower. In addition, nylon 1012 is a flexible polymer with heat resistance, chemical resistance and hydrolysis resistance. The polar amide groups in ordinary nylon molecules have strong water affinity, so the water absorption rate is extremely high. However, the amide group concentration in long-chain nylon 1012 molecules is lower than that of ordinary nylon, and the water absorption rate is low. Therefore, it can maintain excellent toughness and hardness even in a humid environment, and the mechanical properties do not change much. It can maintain excellent dimensional stability in occasions with high requirements and humid environments. In addition, long-chain nylon 1012 molecules have long methyl chains that can be freely extended and rotated, so they have good toughness and softness, high resilience, and high impact toughness and softness even at very low temperatures, so they have excellent bending resistance. Long-chain nylon 1012 has a small friction coefficient and low wear resistance. It will not cause serious wear and obvious wear debris when rubbing against smooth metal surfaces, so long-chain nylon 1012 is particularly suitable as an insulating material for coating copper bars.
[0019] The polyamide-polyether elastomer in the components of the present invention can improve the elongation at break of nylon materials, enhance the adhesion of nylon materials, enable them to firmly adhere to the surfaces of various materials, extend the service life of the product, and maintain good adhesion even after the material is aged.
[0020] The nylon material component of the present invention also contains copolymer PP, wherein the copolymer PP is preferably random copolymer PP, which can improve the impact resistance and transparency of the material, and also solve the problem of the material being easy to bend and turn white. In addition, it also has excellent chemical resistance and electrical properties.
[0021] The invention also improves the oxidation resistance of the material by adding a heat stabilizer, prevents aging, and prolongs the service life of the material.
[0022] The present invention also improves the processing performance and flowability of the modified nylon material by adding a lubricant, so that the nylon material is easier to extrude and coat on the surface of the copper busbar, thereby improving production efficiency.
[0023] Color powder is also added to the components of the present invention, wherein the specific color can be selected according to actual needs, such as orange color powder can be preferably used, and its presence does not affect the performance of other components of the material and meets the color stability requirements of nylon material processing, extrusion coating and subsequent long-term use.
[0024] It should be appreciated that all combinations of the foregoing concepts, as well as additional concepts described in greater detail below, may be considered to be part of the inventive subject matter of the present disclosure, provided such concepts are not mutually inconsistent. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs.
[0026] The words "first", "second" and similar words used in the patent application specification and claims of the present invention do not indicate any order, quantity or importance, but are only used to distinguish different components. Similarly, unless the context clearly indicates otherwise, the singular form of "a", "an" or "the" and similar words do not indicate a quantity limitation, but indicate the existence of at least one. "Include" or "comprises" and similar words mean that the elements or objects appearing before "include" or "comprises" include the features, wholes, steps, operations, elements and / or components listed after "include" or "comprises", and do not exclude the existence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.
[0027] In order to solve the problems of insufficient adhesion, easy blistering, easy bending and whitening, high temperature resistance and easy color change in the application of existing nylon 1012 in copper busbar coating materials, the embodiments of the present invention provide a nylon material for copper busbar coating and a preparation method thereof.
[0028] In the embodiment of the present invention, the nylon material used for copper busbar coating includes the following components in parts by weight: 80-90 parts of long carbon chain nylon 1012, 3-8 parts of polyamide-polyether copolymer elastomer, 5-10 parts of copolymer PP, 1-3 parts of heat stabilizer, 0.5-1.5 parts of lubricant, and 0.4-0.8 parts of color powder.
[0029] In some preferred embodiments of the invention, the number of methylene groups between two amide groups in the main chain repeating unit of the long carbon chain nylon 1012 is 10-15.
[0030] The polyamide-polyether copolymer is a segmented block copolymer composed of polyamide hard segments and polyether soft segments arranged in segments, wherein the polyamide is a crystalline hard segment with a high melting point, and the polyether is an amorphous soft segment with a low glass transition temperature.
[0031] The copolymer PP is preferably a random copolymer PP.
[0032] The heat stabilizer is preferably a non-copper salt heat stabilizer.
[0033] The lubricant is preferably one or more of stearic acid, ethylene bisstearamide, and polyolefin wax.
[0034] The method for preparing a nylon material for coating a copper busbar provided in an embodiment of the present invention comprises the following steps:
[0035] Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, copolymer PP, heat stabilizer, lubricant and color powder according to weight, and dry the long carbon chain nylon 1012 at 90° C.-100° C. for 2-3 hours;
[0036] Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix;
[0037] Step 3: hot-melt extrude the premix in step 1 through a twin-screw extruder, draw into strips, cool, and pelletize to obtain the nylon material. As a preferred processing condition, the processing temperature of the twin-screw extruder is 240°C-260°C.
[0038] The following specific examples are used to compare the performance of the products obtained by the technical solution of the present invention with the existing comparative examples. It can be seen that the various performances of the products obtained by the examples of the present invention are better than those of the comparative examples.
[0039] Example 1
[0040] A nylon material for copper busbar coating includes the following components by weight: 101287.2 parts of long carbon chain nylon, 4 parts of polyamide-polyether copolymer elastomer, 6 parts of copolymer PP, 1.5 parts of heat stabilizer, 0.6 parts of lubricant, and 0.7 parts of color powder. The lubricant is calcium stearate.
[0041] The method for preparing the nylon material according to the embodiment of the present invention comprises the following steps:
[0042] Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, heat stabilizer, lubricant, silicone masterbatch and color powder according to weight, and dry the long carbon chain nylon 1012 at 90° C. for 3 hours;
[0043] Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix;
[0044] Step 3: hot-melt extrude, draw, cool and pelletize the premix in step 1 through a twin-screw extruder to obtain the nylon material, wherein the processing temperature of the twin-screw extruder is 250°C.
[0045] Example 2
[0046] A nylon material for copper busbar coating comprises the following components by weight: 101286.7 parts of long carbon chain nylon, 3 parts of polyamide-polyether copolymer elastomer, 7 parts of copolymer PP, 2 parts of heat stabilizer, 0.5 parts of lubricant and 0.8 parts of color powder, wherein the lubricant is calcium stearate.
[0047] The method for preparing the nylon material according to the embodiment of the present invention comprises the following steps:
[0048] Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, heat stabilizer, lubricant, silicone masterbatch and color powder according to weight, and dry the long carbon chain nylon 1012 at 95° C. for 2.5 hours;
[0049] Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix;
[0050] Step 3: hot-melt extrude, draw, cool and pelletize the premix in step 1 through a twin-screw extruder to obtain the nylon material, wherein the processing temperature of the twin-screw extruder is 260°C.
[0051] Example 3
[0052] A nylon material for copper busbar coating comprises the following components by weight: 101283.7 parts of long carbon chain nylon, 5 parts of polyamide-polyether copolymer elastomer, 8 parts of copolymer PP, 2 parts of heat stabilizer, 0.6 parts of lubricant, and 0.7 parts of color powder, wherein the lubricant is a mixture of ethylene bis stearamide and polyolefin wax.
[0053] The method for preparing the nylon material according to the embodiment of the present invention comprises the following steps:
[0054] Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, heat stabilizer, lubricant, silicone masterbatch and color powder according to weight, and dry the long carbon chain nylon 1012 at 100° C. for 2 hours;
[0055] Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix;
[0056] Step 3: hot-melt extrude, draw, cool and pelletize the premix in step 1 through a twin-screw extruder to obtain the nylon material. The processing temperature of the twin-screw extruder is 250°C.
[0057] Comparative Example 1
[0058] The nylon material of comparative example 1 includes the following components in parts by weight: 101297.8 parts of long carbon chain nylon, 0 parts of polyamide-polyether copolymer elastomer, 0 parts of copolymer PP, 1 part of heat stabilizer, 0.5 parts of lubricant, and 0.7 parts of color powder, wherein the lubricant is calcium stearate.
[0059] The preparation method of the nylon material of the comparative example is the same as the preparation method described in Example 1.
[0060] The performance indicators of the products obtained in Examples 1-3 and Comparative Examples are shown in Table 1 below.
[0061] Table 1 Performance index results of Examples 1-3 and Comparative Examples
[0062]
[0063] Conclusion: It can be seen from Table 1 that the various performance indicators of the modified nylon 1012 material obtained by the technical solution of the present invention are almost equivalent to or better than the performance of the unmodified nylon 1012 material, especially the elongation, which has a significant improvement and enhancement effect, and the coating effect of the product is greatly improved, and both have the excellent effect of no whitening when bent.
[0064] Although the present invention has been disclosed as above with preferred embodiments, it is not intended to limit the present invention. A person with ordinary knowledge in the technical field to which the present invention belongs may make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be determined by the definition of the claims.
Claims
1. A nylon material for copper busbar coating, characterized in that: The invention comprises the following components in parts by weight: 80-90 parts of long carbon chain nylon 1012, 3-8 parts of polyamide-polyether copolymer elastomer, 5-10 parts of copolymer PP, 1-3 parts of heat stabilizer and 0.5-1.5 parts of lubricant.
2. The nylon material for copper busbar coating according to claim 1, characterized in that: The number of methylene groups between two amide groups in the main chain repeating unit of the long carbon chain nylon 1012 is 10-15.
3. The nylon material for copper busbar coating according to claim 1, characterized in that: The polyamide-polyether copolymer is a segmented block copolymer composed of polyamide hard segments and polyether soft segments arranged in segments, wherein the polyamide is a crystalline hard segment with a high melting point, and the polyether is an amorphous soft segment with a low glass transition temperature.
4. The nylon material for copper busbar coating according to claim 1, characterized in that: The copolymer PP is a random copolymer PP.
5. The nylon material for copper busbar coating according to claim 1, characterized in that: The heat stabilizer is a non-copper salt heat stabilizer.
6. The nylon material for copper busbar coating according to claim 1, characterized in that: The lubricant is one or more of stearic acid, ethylene bisstearamide, and polyolefin wax.
7. The nylon material for copper busbar coating according to claim 1, characterized in that: It also includes 0.4-0.8 parts of color powder.
8. A method for preparing a copper busbar coated with nylon material, characterized in that: The following steps are involved: Step 1: Weigh long carbon chain nylon 1012, polyamide-polyether copolymer elastomer, copolymer PP, heat stabilizer, lubricant and color powder according to weight, and dry the long carbon chain nylon 1012 at 90° C.-100° C. for 2-3 hours; Step 2: Put the dried long carbon chain nylon 1012 and the other components into a mixer and mix them evenly to obtain a premix; Step 3: hot-melt extrude the premix in step 1 through a twin-screw extruder, draw into strips, cool, and pelletize to obtain the nylon material.
9. The nylon material for copper busbar coating according to claim 8, characterized in that: The processing temperature of the twin-screw extruder is 240°C-260°C.